2020
DOI: 10.3390/app10072609
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Behavior of Concrete-Filled Circular Steel Tubular Column–Reinforced Concrete Beam Frames with Recycled Aggregate Concrete

Abstract: The application of recycled aggregate concrete (RAC) in concrete filled steel tubular (CFST) structures can eliminate the deterioration of concrete performance caused by the original defects of the recycled aggregate, which also provides an effective way for the recycling of waste concrete. In this paper, a test of a small scale model of a circular CFST column-reinforced concrete (RC) beam frame with RACs under low cyclic loading was presented in order to investigate its seismic behavior. The failure modes, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…For a building, the load due to gravity can be regarded as vertical load, the transmission path of the vertical load in the building structure from top to bottom is "floor -beam -column -foundation". The upper load of the building must pass through the beam-column joint [9] when the vertical load is transmitted downward [12]. When the vertical load is transmitted to the beam-column joint, the contact surface of the load suddenly becomes smaller, and the stress will also change greatly.…”
Section: Concrete Beam-column Jointsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a building, the load due to gravity can be regarded as vertical load, the transmission path of the vertical load in the building structure from top to bottom is "floor -beam -column -foundation". The upper load of the building must pass through the beam-column joint [9] when the vertical load is transmitted downward [12]. When the vertical load is transmitted to the beam-column joint, the contact surface of the load suddenly becomes smaller, and the stress will also change greatly.…”
Section: Concrete Beam-column Jointsmentioning
confidence: 99%
“…Mou et al [8] conducted experiments on a new beam to reinforced concrete-filled steel tube column joint and found through experiments that the cross section of the transfer sleeve in the column node was the key factor affecting the strength of the beam-column node. Chen et al [9] investigated the seismic performance of a circular concrete an et al [7] proposed a joint type of concrete-filled square steel tubular columns and filled steel tubular column-reinforced concrete beam frame under low cyclic loading and found through tests that the design method of the recycled aggregate concrete filled circular steel tube frame met the seismic design requirements of a stronger joint followed by the stronger column and the weaker beam and the frame had has good collapse resistance and energy dissipation capacity. In this paper, concrete beam-column joints were briefly introduced, the seismic performance of concrete beam-column joints was strengthened by a steel skeleton, and concrete beam-column joints and reinforced concrete beam-column joints were prepared for experimental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the method's applicability to S‐RACFST frame has largely gone unexplored. An experimental investigation on circular RACFST was done by Chen et al 32 and Wen et al 33 The structural performance of the S‐RACFST was discussed by Li et al 34 in comparison to the circular specimen reported by Chen et al 32 The S‐RACFST frame has been determined to have the qualities of a high bearing capacity, good ductility, and superior seismic performance. In this paper, based on summarizing the previous research, the inter‐story displacement angle limit value was adopted as the quantitative index of each performance level, and the specific steps of displacement‐based seismic design of S‐RACFST frame structure were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the existence of blocks reduces the bearing capacity and hysteretic properties of specimens when compared with all cast-in-place columns. Regarding cast-in-place concrete, Chen et al [ 22 ] researched the seismic behavior of the RACFST circular frames. The frames demonstrated optimal deformation performance, collapse resistance, and energy dissipation capacity.…”
Section: Introductionmentioning
confidence: 99%